Laminated triboelectric acoustic energy harvester based on electrospun nanofiber towards real-time noise decibel monitoring. (August 2022) - Xu, Wenkai; Guo, Jiangtao; Wen, Haiyang; Meng, Xianghe; Hong, Hongxin; Yuan, Jingbo; Gao, Jiaan; Liu, Dingyu; Ran, Qing; Wang, Yudi; Duan, Jialong; Tang, Qunwei; et al.
Abstract: Acoustic energy is an indispensable environmental energy source, which is pollution-free, widely distributed and is ultimately dissipated into thermal energy at the propagation stag. Generally, incident sound power density is relatively low and structural design for acoustic energy harvesting is crucial. Based on the principle of coupling between contact electrification and electrostatic induction, the invention of triboelectric nanogenerators (TENG) becomes a good resolution to capture acoustic energy efficiently. This work developed a laminated electrospun nanofibers triboelectric acoustic energy harvester (LEN-TAEH) toward self-powered real-time noise decibel monitoring. Through optimizing the porosity, dielectric property of electrospun nanofibers, laminated structure and the configuration parameters of the LEN-TAEH, a maximum V oc of 124 V and I sc of 23.5 μA can be obtained by one individual LEN-TAEH with maximum charging rate of 11.5 μC/s, and around 100 LEDs can be lighted up simultaneously under resonance frequency of 200 Hz and optimal sound intensity level of 104 dB. Furthermore, by stacking two units to form a two-stack LEN-TAEH can register a V oc of 170 V, power density of 1.28 W/m 2 and a sensitivity of 53.6 V/Pa under resonance frequency. In addition, the LEN-TAEH behaved excellent working stability and durability with the working output performances remaining above 90% after 30 days of continuous operation. Finally, the functions of real-time noise decibel monitoring and voice recognition are realized under stimulation of different frequencies and sound intensity level, demonstrating the promising application potential of the LEN-TAEH as noise sensor towards self-powered environmental noise monitoring. Graphical Abstract: Laminated triboelectric acoustic energy harvester based on electrospun nanofiber towards real-time noise decibel monitoring. ga1 Highlights: Laminated electrospun nanofibers triboelectric acoustic energy harvester (LEN-TAEH) is developed-time decibel monitoring Porosity, dielectric property and structure configuration parameters are systematically investigated and optimized Maximum V oc of 124 V can be obtained by individual LEN-TAEH with charging rate of 11.5 μC/s and 100 LEDs can be lighted up V oc of 170 V, power density of 1.28 W/m 2 and sensitivity of 53.6 V/Pa can be obtained by two-stack LEN-TAEH Excellent working stability and durability for the LEN-TAEH with V oc remaining above 90% after 30 days operation